Remarks by Michael Smart. (2017) - Smart, Michael
Abstract : More than enough. That's the silver lining, of course. But, you know, I think the answer to your question, Gary, at least as it relates to trade negotiations, is emphatically yes, we are in a slower period than the administration anticipated. I don't think the explanation is that different from healthcare or taxes or Syria. I mean, it's just a lot more complicated, I think, than the administration realized. I was told that when they returned from one of their first Hill briefings on trade, one of the briefers remarked, "Who knew Congress cared so much about agriculture?" a point that Warren made. And that's really just the tip of the iceberg, because there's many things on the agenda.